University of British Columbia Herbarium (UBC) - Algae Collection from University of British Columbia ... - Jennings, Linda (University of British Columbia, 2013)
This dataset includes all digitized algae in the UBC collection, encompassing approximately 80% of the collection. During the course of Robert Scagel’s academic career (1952-1986) and assisted by graduate students and postdoctoral fellows carrying out research on benthic marine algae, Scagel oversaw the expansion of the Phycological Herbarium to its present size of over 67,000 specimens. During this period, with support from U.B.C., the National Research Council of Canada (NSERC), the Defence Research Board of Canada, the Fisheries Research Board of Canada, the Provincial Fisheries Department, the B.C. Research Council and the National Science Foundation (U.S.), collecting activities were carried out all along the Pacific Coast from central California to Alaska, including the Aleutian Islands as far west as Attu Island. Collections from these surveys were deposited in the Phycological Collection at U.B.C. The Alaska representation in the Phycological Collection has been significantly augmented since 1986 by ...